Global translational landscape of the Candida albicans morphological transition. Issue 2 (24th December 2020) - Mundodi, Vasanthakrishna; Choudhary, Saket; Smith, Andrew D; Kadosh, David
Abstract : Candida albicans undergoes a reversible transition from single budding yeast to filamentous cells that is required for virulence. Here, Mundodi et al use ribosome profiling to determine the first global translational profile associated with the C. albicans morphological transition. They find that many important virulence factors strongly induced at the transcriptional level show significantly reduced translational efficiency. Overall, their findings suggest that key virulence processes in C. albicans, and most likely other fungal pathogens, are under widespread translational control. Abstract: Candida albicans, a major human fungal pathogen associated with high mortality and/or morbidity rates in a wide variety of immunocompromised individuals, undergoes a reversible morphological transition from yeast to filamentous cells that is required for virulence. While previous studies have identified and characterized global transcriptional mechanisms important for driving this transition, as well as other virulence properties, in C. albicans and other pathogens, considerably little is known about the role of genome-wide translational mechanisms. Using ribosome profiling, we report the first global translational profile associated with C. albicans morphogenesis. Strikingly, many genes involved in pathogenesis, filamentation, and the response to stress show reduced translational efficiency (TE). Several of these genes are known to be strongly induced at the transcriptional level, suggesting that a translational fine-tuning mechanism is in place. We also identify potential upstream open reading frames (uORFs), associated with genes involved in pathogenesis, and novel ORFs, several of which show altered TE during filamentation. Using a novel bioinformatics method for global analysis of ribosome pausing that will be applicable to a wide variety of genetic systems, we demonstrate an enrichment of ribosome pausing sites in C. albicans genes associated with protein synthesis and cell wall functions. Altogether, our results suggest that the C. albicans morphological transition, and most likely additional virulence processes in fungal pathogens, is associated with widespread global alterations in TE that do not simply reflect changes in transcript levels. These alterations affect the expression of many genes associated with processes essential for virulence and pathogenesis.